STUDY OF SEDIMENT GENESIS BASED ON BOREHOLE LOGGING DATA AND EVALUATION OF THE RELATIONSHIP BETWEEN SEDIMENT GENESIS AND RESERVOIR PROPERTIES - KERİMOVA, Kifayet and KHALILOVA, Lala (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The Bulla-Deniz field is one of the most promising from the point of view of oil and gas content in the South Caspian Trough. It is located in the northern part of the Baku Archipelago. Despite the fact that the Bulla-Deniz field, characterized by deep wells, has been in operation since 1975, it has not yet been fully explored. Its geological structure has been studied on the basis of complex geophysical exploration works, structural mapping, exploration drilling and production material. The wells have penetrated the sediments of the Productive Series (PS) only up to the upper part of the Kirmaky Suite. Deposits of the Sub-Kirmaky and Qala Suites have not been penetrated in the field area. Oil and gas content within the Bulla-Deniz field is confined to horizons V, VII and VIII of the PS. VIII horizon, according to Apsheron stratigraphic scheme, corresponds to the Upper Kirmaky Sandy complex and is represented by two sandy-silty strata in the bottom and top parts. Horizon VII corresponds to the Fasila Suite and is composed predominantly of sandstones. The V horizon (in accordance with the Apsheron section corresponds to horizons VIII–IX) is represented by alternation of thick layers of sand, sandstone and clay. Such major issues as assessment of sedimentation conditions and genesis of the rocks forming these horizons, as well as establishing the relationship between the genetic origin of rocks and their reservoir properties, remain relevant at present. One of the most urgent goals today is to conduct geophysical research related to oil and gas field prospecting and exploration using more advanced methods and introducing new technologies. It allows to determine the internal structure of oil and gas bearing structures and oil-bearing horizons with greater accuracy on the basis of field geophysics data. Methods. Due to intensification of prospecting and exploration works aimed at identification of oil and gas bearing formations and horizons of Productive Series, there is need to apply modern methodological and interpretative approaches – tectonic, eustatic, stratigraphic and genetic analyses – as an alternative to expensive drilling. From this point of view, determination of sedimentation conditions of horizons and reservoir complexes of the Productive Series is important for a targeted search for oil and gas deposits not associated with anticlinal traps, identification of stratigraphic, lithologic, paleogeomorphologic, epigenetic and other hard-to-recognize traps, as well as for assessment of oil and gas bearing prospects of the studied region and analysis of the distribution of potentially interesting objects within sedimentary basins. On the other hand, there is a definite relationship between the lithological and mineralogical composition of rocks and their reservoir properties, which ultimately manifests itself in the petrophysical characteristics of reservoir rocks. For this reason, the study of the relationship between the genesis of sediments of the productive strata and their reservoir properties makes it possible to predict the patterns of distribution of sandy material over the area, as well as to draw conclusions about the nature of the development of porous and permeable zones. This, in turn, has important scientific and practical significance for assessing the nature of changes in the reservoir properties of sedimentary rocks. It is from this point of view that the article proposes a rational approach to identifying the relationship between the genetic origin of sediments and reservoir properties of rocks on the basis of quantitative interpretation of complex well data using the "quantitative model of log facies". Horizons V, VII and VIII of the Productive Series of the Bulla-Deniz field were considered as the object of the research. The results of the research are presented and analyzed from the point of view of assessing the genesis of sediments and their influence on the filtration-capacitance properties of rocks. Results. Using a quantitative log facies model, lithofacies interpretation of well sections X1, X2, X3, X4 and X5 of the conditional area of the Bulla-Deniz field was carried out. During the analysis alluvial stream facies, bars, coastal-beach and shelf (coastal-marine) formations were identified. The relationship between the genetic origin of sedimentary rocks and their reservoir properties was established. The results showed that the physical properties of the studied rocks are directly related to their genesis. Histograms reflecting changes in average relative sandiness and porosity, as well as variation in the thickness of stream facies, bars and beach deposits along the sections of the studied wells were also constructed. Conclusions. A comprehensive lithofacies and seismic facies analysis was carried out for the Bulla-Deniz field using data from wells X1–X5 and seismic profiles. Facies of stream, bar, coastal-beach, and shelf origin were identified. A clear relationship was established between the genetic origin of sediments and their reservoir properties, particularly in stream and bar facies, where effective porosity and sand body thickness show strong correlation. In contrast, coastal-beach facies exhibit chaotic variation, lacking such correlation. Additionally, seismic facies analysis within the Lower Pliocene interval revealed fluvial, marine, and mixed sedimentation environments, indicating a complex depositional history in the study area.